Lethal and sublethal effects of a methomyl-based insecticide in Hoplobatrachus rugulosus - Waret Trachantong (2018)
© 2017 The Japanese Society of Toxicologic Pathology. The aim of this study was to investigate the lethal and sublethal toxicity of a methomyl-based insecticide in Hoplobatrachus rugulosus, as methomyl-based insecticides are applied in massive amounts and agrochemicals have effects on the decline in amphibian populations. To evaluate the toxic effects of methomyl from agricultural application, a methomyl-based insecticide containing 40% methomyl was selected. The median lethal concentration of 96 hours of methomyl exposure was 8.69 ppm for H. rugulosus tadpoles. The lethal concentration also produced severe histological damage in the livers and kidneys of the exposed tadpoles. The sublethal concentration used for methomyl was 144 ppb during the metamorphosis period. It was found that the sublethal concentration of the methomyl compound could decrease growth, metamorphosis time, and size, disturb biochemical parameters, and produce histological damage. In livers, methomyl effects increased oxidative stress and dramatically decreased the glycogen level of the treated froglets. Mononuclear infiltration, blood congestion, amorphous substances, and hepatocytes vacuolization were observed throughout liver tissue. The methomyl-based insecticide also increased oxidative stress and decreased nitric oxide levels in the kidneys of the exposed froglets. Renal tissue damage including blood congestion, amorphous substances, and Bowman’s capsule spaces reduction were found in the methomyl exposure group. The methomyl compound also produced vacuoles in various stages of oocytes, but no histological damage was found in testicular tissue. Our results indicated strong toxic effects of the methomyl-based insecticide on H. rugulosus, a broadly tolerant anuran.